2010
DOI: 10.1002/bjs.7095
|View full text |Cite
|
Sign up to set email alerts
|

Optical scanning for rapid intraoperative diagnosis of sentinel node metastases in breast cancer

Abstract: In this proof-of-principle study, the ESS results were comparable with current intraoperative diagnostic techniques of lymph node assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…These techniques include fluorescence molecular imaging [7], elastic scattering spectroscopy [8,9] and optical coherence tomography (OCT) [1013]. In previous studies, metastatic deposits in lymph nodes imaged with OCT were observed as regions of higher scattering relative to surrounding normal tissue, confirmed by comparison to histological sections [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques include fluorescence molecular imaging [7], elastic scattering spectroscopy [8,9] and optical coherence tomography (OCT) [1013]. In previous studies, metastatic deposits in lymph nodes imaged with OCT were observed as regions of higher scattering relative to surrounding normal tissue, confirmed by comparison to histological sections [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Probing depths range from 0.5–2mm, depending on the tissue optical properties and source-to-detector distance in the array[27]. Initial efforts here and by others have employed stepper motors to raster scan the tissue sample across a more localized beam (100–200μm spot size), but significant limitations were imposed upon data acquisition time and field size [30, 31]. The Raman molecular fingerprint has also been used for point-based diagnostic sensing in the tumor resection cavity, first by Haka et al [26] and later by Keller et al [32], who demonstrated detection of breast cancers up to 2mm below a normal tissue layer with a spatially offset source-detector pair.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ability to translate tissue morphology into spectral features at the cellular and sub‐cellular levels, ESS relates directly to the observed tissue architecture and structure of histopathologic features . Different tissue types and histopathological status exhibit specific optical signatures, and ESS has been demonstrated clinically to assess malignancy in multiple tissue types . Spectral correlation with histopathologic diagnosis using variations of ESS has also been reported by other groups .…”
Section: Introductionmentioning
confidence: 87%